2015
DOI: 10.1007/s10549-015-3452-x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in tamoxifen pharmacokinetics in mice and breast cancer patients

Abstract: The anti-estrogen tamoxifen is characterized by a large variability in response, partly due to pharmacokinetic differences. We examined circadian variation in tamoxifen pharmacokinetics in mice and breast cancer patients. Pharmacokinetic analysis was performed in mice, dosed at six different times (24-h period). Tissue samples were used for mRNA expression analysis of drug-metabolizing enzymes. In patients, a cross-over study was performed. During three 24-h periods, after tamoxifen dosing at 8 a.m., 1 p.m., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
(30 reference statements)
3
18
0
1
Order By: Relevance
“…; Binkhorst et al. ). The plasma half‐life of tamoxifen and endoxifen in adult mice is 6–7 h after a single oral dose of 20–200 mg/kg tamoxifen; a 200 mg/kg dose is completely cleared of all bioactive forms within 2–3 days (Robinson et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Binkhorst et al. ). The plasma half‐life of tamoxifen and endoxifen in adult mice is 6–7 h after a single oral dose of 20–200 mg/kg tamoxifen; a 200 mg/kg dose is completely cleared of all bioactive forms within 2–3 days (Robinson et al.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to food, the time of drug intake influences tamoxifen and endoxifen metabolism. Binkhorst and colleagues reported 15% and 3% higher endoxifen and tamoxifen systemic exposure (AUC 0-24 ) when tamoxifen was taken in the morning, whilst more balanced concentrations were found in the evening schedule [87]. Regardless of these differences, the authors concluded this phenomenon would probably not be clinically important for tamoxifen efficacy.…”
Section: Food Circadian Rhythm and Seasonal Variationmentioning
confidence: 99%
“…Gene ESR2 codes for estrogen receptor 2 ( β ) and, in its promoter, contains a known SNP marker (rs35036378) for prophylactic treatment (with tamoxifen) of an ESR2-deficient primary tumor pT1 [ 87 ] to prevent progression to breast cancer [ 88 ]; this treatment is characterized by a circadian optimum for its use [ 89 ]. A keyword search yielded basic research findings of circadian disturbances of daytime behavioral activity in ESR2-deficient female mice [ 90 ].…”
Section: Resultsmentioning
confidence: 99%